Chameleon-linguist and the revival of casuistry: afterthoughts on a controversial suggestion by Fernando Tarallo - Rajagopalan, Kanavillil (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
1079/5000 This paper seeks to rediscuss the controversial question raised by Fernando Tarallo regarding how to adapt a linguistic theory to the unexpected specificities that concrete cases - the so-called "real facts" - tend to present. Tarallo’s suggestion that it is necessary in these cases to use a good deal of practical sense and to be, say, a ’chameleon linguist’, is reviewed in the light of research by Jansen and Toulmin (1988). According to these authors, the rediscovery of ’casuism’ - free from the negative connotations that the history of thought has given it - opens up excellent possibilities for us to break free from the doldrums created by totalizing theories with their supposedly universal goals that can barely keep up with the obligation obligation. to adapt to the lived experience. At the same time as the idea launched by Tarallo is searched for the germ of causism (albeit unintentionally, by far), it is also argued that Jonsen and Toulmin’s thesis meets the contemporary yearning for the current that we call it ’postmodernity’.